Suffering of the health team in a hospital context: caring for professional carers - Kovács, Maria Julia (O Mundo da Saúde, 2010)
This paper discusses death in the Twenty-first century such as health professionals face it and the consequences in their physical and psychological health. Death it is seen as an enemy, hidden, shameful, injuring the omnipotence of modern man. It is a prohibited subject disturbing communication between patients, relatives and professionals. With the advancement of medicine, death takes place in the hospital setting. The daily life of health professionals regarding death implies difficult choices to make, producing additional stress. In the mentality of interdicted death there is not an authorized expression of emotions and pain, leading to diseases and an increase of cases of depression, leading to a greater incidence of Burnout Syndrome among professionals. They choose to work with death and dying, bringing in their own way of dealing with pain and losses. Fail to avoid death or relieve suffering brings professionals to be aware of their finitude. A relationship is established between intense stress, collapse and non recognized mourning. Some professionals do not accept or recognize their own mourning. Palliative care programs try to modify this dysfunction by encouraging group work in caring for patients and their families. A proposal of care is presented for carers aiming at: a) Training and sensitization to talk about the main difficulties; b) Deepening the subject brought by the group; c) Projecting care for carers according to the work team, having in mind their necessities; d) The methodology for the several phases of the work was promoting group activities. A kind of care is psychological duty, which facilitates the growth and the development of the person, implying empathy, acceptance and congruence. It offers a space for listening that uses qualified persons as soon as people ask for help, welcoming the demand. Other forms of care are presented: leisure activities, psychotherapy and psychological care, courses and workshops favoring significant apprenticeship, individual supervision and group supervision for difficult cases, always reflecting about care and favoring team work.